2019
DOI: 10.1002/1873-3468.13321
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures and biochemical analyses of intermediate cleavage peptidase: role of dynamics in enzymatic function

Abstract: Intermediate cleavage peptidase (Icp55) processes a subset of mitochondrial matrix proteins by removing a bulky residue at their N termini, leaving behind smaller N‐terminal residues (icp activity). This contributes towards the stability of the mitochondrial proteome. We report crystal structures of yeast Icp55 including one bound to the apstatin inhibitor. Apart from icp activity, the enzyme was found to exhibit Xaa‐Pro aminopeptidase activity in vitro. Structural and biochemical data suggest that the enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Peptidase M24 proteins superfamily members have multiple biological functions in animals, plants, and microorganisms, and are an emerging gene family. In plants, the functions of most members of the peptidase M24 superfamily are not known in detail, but studies have shown that these genes are involved in a variety of biological processes, such as participating in the protein synthesis process [25,29,[48][49][50][51], ensuring the normal development of plant organs [14,28,32,52,53], regulating the formation of special structures in legumes [54], abiotic response and biotic stress [15,16,34,54]. Therefore, this study aimed to identify and classify the members of the peptidase M24 in wheat, explore the role of TaM24 genes in drought and salt stress in Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
“…Peptidase M24 proteins superfamily members have multiple biological functions in animals, plants, and microorganisms, and are an emerging gene family. In plants, the functions of most members of the peptidase M24 superfamily are not known in detail, but studies have shown that these genes are involved in a variety of biological processes, such as participating in the protein synthesis process [25,29,[48][49][50][51], ensuring the normal development of plant organs [14,28,32,52,53], regulating the formation of special structures in legumes [54], abiotic response and biotic stress [15,16,34,54]. Therefore, this study aimed to identify and classify the members of the peptidase M24 in wheat, explore the role of TaM24 genes in drought and salt stress in Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
“…The equilibrium established between a monomer and its corresponding dimer is a fundamental process involved in crucial steps in biochemical and chemical transformations. From mitochondrial, 1 DNA 2 and enzymatic functions 3 to the proliferation of cancer cells, 4–6 and the mechanisms involved in diseases such as Parkinson, 7 malaria, 8 and others, 9 monomer–dimer equilibria are invoked. In transition metal catalysis, dissociative processes of dimeric complexes to unsaturated intermediates are often postulated as yielding catalytically active species.…”
Section: Introductionmentioning
confidence: 99%
“…1 H NMR (500 MHz, C 6 D 6 , 298 K): δ 7.48-7.37 (m, 5H, CH arom ), 7.13-6.97 (m, 31H, CH arom ), 2.58-2.24 (m, 4H, CH 2 ), 1.80 (sept, J HH = 7.1 Hz, 4H, CH-i Pr), 1.49 (d, J HH = 7.6 Hz, 6H, CH 3 -i Pr), 1.41 (d, J HH = 6.8 Hz, 6H, CH 3 -i Pr), 0.84 (d, J HH = 7.5 Hz, 12H, CH 3 -i Pr), 0.60 (d, J HH = 7.4 Hz, 6H, CH 3 -i Pr), 0.38 (d, J HH = 7.5 Hz, 6H, CH 3 -i Pr), 0.10-0.02 (m, 2H, CH-i Pr), ppm 31. P{ 1 H} NMR (202.46 MHz, C 6 D 6 ): 49.04 (d, J PRh = 164.0 Hz) ppm.…”
mentioning
confidence: 99%